EVALUASI EFEKTIVITAS MEDIA SOSIAL DAN WORD OF MOUTH DALAM PROMOSI WISATA BUKIT SANGHYANG DORA DI KABUPATEN MAJALENGKA - Syifa Ayu Salsabilla; Ilham Gemiharto; Samson CMS (Linimasa : Jurnal Ilmu Komunikasi, 2025)
This study aims to determine the utilization of promotional media, especially social media and word of mouth (WOM) carried out by the manager of Bukit Sanghyang Dora tourism. The subjects of this research were the manager of Sanghyang Dora hill tour and five visitors to Sanghyang Dora hill tour. The object of this research is the utilization of promotional media, especially social media and word of mouth (WOM) in the promotion of Bukit Sanghyang Dora tourism. The method used in this research uses a qualitative method with a case study approach. Data collection is done by interview, observation, and documentation. The results and discussion in this study use the Ellaboration Likelihood Model theory. The results of this study indicate that the promotion of Bukit Sanghyang Dora using social media, especially Instagram, is considered effective in disseminating information and attracting tourists' attention. Word of mouth (WOM) plays an important role as a trusted source of information. Social media, used to attract attention through visual content, interactive features such as stories and reels, is effective in reaching the audience. Word of mouth (WOM) complements promotion by providing reliable information from previous visitors' experiences, which can build and increase interest in visiting